2006
DOI: 10.1021/la061326+
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Photosystem I within Self-Assembled Films

Abstract: We have developed a process to incorporate an integral membrane protein, Photosystem I (PSI), into an organic thin film at an electrode surface and thereby insulate the protein complex on the surface while mimicking its natural environment. The PSI complex, which is primarily more hydrophobic on the exterior than interior, is hydrophobically confined in vivo within the thylakoid membrane. To mimic the thylakoid membrane and entrap PSI on an electrode, we have designed a series of steps using a thin self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 64 publications
0
43
0
1
Order By: Relevance
“…The photocatalytic functionality of this vastly abundant and widely accessible protein has found utility in processes other than photosynthesis, such as bio‐hybrid systems that use light‐energy to produce hydrogen,6–9 as well as photoelectrochemical10–16 and photovoltaic17–22 systems that generate light‐induced increases in electrical currents and voltages. Many of these initial studies investigated the functionality of monolayers of PSI complexes assembled onto various substrates 12, 16, 17, 19, 22–25. Additional work by our group11 and others14 has shown how photocurrents produced by PSI monolayers in electrochemical systems may be enhanced by decorating nanostructured electrodes with PSI because the increased surface area of the substrates could accommodate more PSI complexes than a planar surface of similar geometric area.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic functionality of this vastly abundant and widely accessible protein has found utility in processes other than photosynthesis, such as bio‐hybrid systems that use light‐energy to produce hydrogen,6–9 as well as photoelectrochemical10–16 and photovoltaic17–22 systems that generate light‐induced increases in electrical currents and voltages. Many of these initial studies investigated the functionality of monolayers of PSI complexes assembled onto various substrates 12, 16, 17, 19, 22–25. Additional work by our group11 and others14 has shown how photocurrents produced by PSI monolayers in electrochemical systems may be enhanced by decorating nanostructured electrodes with PSI because the increased surface area of the substrates could accommodate more PSI complexes than a planar surface of similar geometric area.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, our recent studies have revealed that protein concentrations and driving forces play a significant role in altering the morphological assembly of PS I on SAM substrates when adsorbed from aqueous buffer solutions using gravity driven or electric field assisted directed deposition [4]. Commonly used self-assembly of PS I from buffer solutions onto hydroxyl-terminated alkanethiolate SAM/Au surfaces [3,[32][33][34][35] and a few directed attachment of PS I to Au substrates using platinization techniques [36] have analyzed the attachment dynamics based on surface characterizations using microscopy (AFM) or spectroscopic techniques. Yet, our recent dynamic light scattering (DLS) data have demonstrated that the complex surface morphologies observed in most of these studies mainly arise due to protein-protein interactions in the solution phase [4].…”
Section: Introductionmentioning
confidence: 99%
“…With help of the tag, the construction was immobilized on a gold electrode containing self-assembling layer of alkanethiols with a head part as Ni-NTA. It was shown experimentally that the proximity of RCs to the electrode is important for the cell effective operation (Kincaid et al, 2006).…”
Section: Methods Of Immobilization and Orientation Of Biocatalystsmentioning
confidence: 99%
“…Many techniques were used for immobilization of photosynthetic complexes, including in particular, bioelectrocatalystic self-assembling monolayers (bio-SAMs) (Nakamura et al, 2000;Kincaid et al, 2006;Frolov, et al, 2008;Mershin et al, 2012); Ni-NTA was attached to polyhistidine tagged PS1 complexes (Fig. 4d) (Das, 2004;Sekar et al, 2014); the redox-active hydrogels (Badura et al, 2008); and fixation on CNTs by means of molecular binding reagents .…”
Section: Methods Of Immobilization and Orientation Of Biocatalystsmentioning
confidence: 99%